Penelitian Tentang Instagram - Kartini Kartini; Juwita Syahrina; Nisya Siregar; Nurhasanah Harahap (Maktabatun: Jurnal Perpustakaan dan Informasi, 2022)
In the digital era like today, there are many applications that can be used as fields to make money, one of which is Instagram social media which is now an alternative media in the field of marketing and promotion. Broadly speaking, everyone can do business through Instagram social media. Instagram disseminates photos and videos with the features presented and the most popular social media. The advantage presented by social media Instagram is that it is able to reach most other social media users. Instagram social media offers a communication system with various ease of use features or content. This study aims to 1) find out more about the use of Instagram, 2) find out the various features of Instagram, 3) find out the benefits of Instagram as a promotion place in the library.